Doktrin Gereja (Eklesiologi) - Sarmauli; Ameliatera; Jeni Utary; Sopiani; Sella Vinisya (Journal of Cultural Relativism (JCR), 2024)
The church is a spiritual container where saved people enter into the fellowship of the Body of Christ. The word "church" itself comes from the Greek word "Ekklesia", where people from various cultural backgrounds with a world environment and a pluralistic society receive the gospel message voluntarily with the help of the Holy Spirit, and enter a spiritual and pluralistic community. During the time of the Church Fathers, the Church was often referred to as the communia sanctorum, namely the people of God whom he had chosen to be his own. During the Reformation period. The reformers opposed the concept of a Catholic church, but there were divisions among the reformers.Luther viewed the church as a spiritual community of believers in Christ, and Luther updated the biblical understanding of the priesthood of all believers.